Water use efficiency of Manihot Esculenta Crantz under drip irrigation system in South Western Nigeria. - Olanrewaju, O.O.; Olufayo, A.A.; Oguntunde, P.G.; Ilemobade, A.A. (EuroJournals, Inc., 2009)
Field experiments was conducted at Teaching and Research Farm, Federal University of Technology, Akure between November 2006 and November 2007 to find out the water use efficiency under drip irrigation system and effect on the growth and yield of Cassava (Manihot esculenta Crantz). A popular hybrid of cassava TMS 30572 was tried as a test crop. The soil of the experimental site was moderately drained, loamy sand. The experiments were laid out in a 4 × 4 × 2 randomised complete block design (RCBD) consisting of 4 treatments, 4 replicates and 2 varieties using a spacing of (1m × 0.8m) for mechanical harvesting. The results indicated that the highest moisture content was recorded at depth of 40cm during the late stage of tuber development and the highest biomass yield was recorded under full irrigation treatment than in other treatments. The yield of cassava ranged from 21.87 to 14.13 t ha-1 in all the treatments except for the control that has 8.45 t ha-1 while the water use efficiency ranged from 19.18 to 23.63 kg ha-1mm. Irrigation through full treatment registered the highest mean tuber yield of 21.87 t ha-1 while the least tuber yield was associated with the control treatment. The height and stem diameter of cassava also responded higher under full treatment of available water. This study demonstrated that medium irrigation (60% AW) could be best option in terms of water efficiency.
Keywords: Irrigation; Manihot Esculenta Crantz; Water Use Efficiency; Yield; Irrigation management